Correction: Assessing Progress, Impact, and Next Steps in Rolling Out Voluntary Medical Male Circumcision for HIV Prevention in 14 Priority Countries in Eastern and Southern Africa through 2014. - Katharine Kripke; Emmanuel Njeuhmeli; Julia Samuelson; Melissa Schnure; Shona Dalal; Timothy Farley; Catherine Hankins; Anne G Thomas; Jason Reed; Peter Stegman; Naomi Bock (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0158767.].